The [13C]octanoic acid breath test for gastric emptying quantification: A focus on nutrition and modeling. Issue 4 (7th July 2022) - von Gerichten, Johanna; Elnesr, Marwan H.; Prollins, Joe E.; De Mel, Ishanki A.; Flanagan, Alan; Johnston, Jonathan D.; Fielding, Barbara A.; Short, Michael
Abstract: Gastric emptying (GE) is the process of food being processed by the stomach and delivered to the small intestine where nutrients such as lipids are absorbed into the blood circulation. The combination of an easy and inexpensive method to measure GE such as the CO2 breath test using the stable isotope [ 13 C]octanoic acid with semi‐mechanistic modeling could foster a wider application in nutritional studies to further understand the metabolic response to food. Here, we discuss the use of the [ 13 C]octanoic acid breath test to label the solid phase of a meal, and the factors that influence GE to support mechanistic studies. Furthermore, we give an overview of existing mathematical models for the interpretation of the breath test data and how much nutritional studies could benefit from a physiological based pharmacokinetic model approach.